MODEL PENDIDIKAN KEWIRAUSAHAAN DI PERGURUAN TINGGI DALAM MENUMBUHKAN ENTREPRENEUR MUDA KREATIF DAN INOVATIF DI KOTA SEMARANG (Faculty of Social Science, Universitas Negeri Semarang, 2012)
Thought to bring entrepreneurial education, both integrated in the curriculum and through student activities, was developed by several universities. It is targeted in 2014 that as many as 20 percent of college graduates managed to become a businessman. Creation of entrepreneurs community among lecturers and college graduates is intended to accelerate the addition of the number of entrepreneurs in Indonesia needed to drive economic growth in the nation. Associated with improving the quality and relevance of education, which basically includes the development of the moral aspects, morals, mind, character, knowledge, skills, health, art and culture, the development of these aspects, leads to the improvement and development of life skills, which is realized through the achievement of basic competencies to survive, and able to adapt in order to succeed in life. But in reality the educational institutions have not been able to solve the problem of unemployment and bridging the education and business.